3D impedimetric sensors as a tool for monitoring bacterial response to antibiotics. Issue 8 (18th March 2019) - Brosel-Oliu, S.; Mergel, O.; Uria, N.; Abramova, N.; van Rijn, P.; Bratov, A.
Abstract : A novel strategy for selective immobilization of bacteria on a 3D impedimetric transducer for sensing antimicrobial reagents. Abstract : The presence of antimicrobial contaminants like antibiotics in the environment is a major concern because they promote the emergence and the spread of multidrug resistant bacteria. Since the conventional systems for the determination of bacterial susceptibility to antibiotics rely on culturing methods that require long processing times, the implementation of novel strategies is highly required for fast and point-of-care applications. Here the development and characterization of a novel label-free biosensing platform based on a microbial biosensor approach to perform antibiotic detection bioassays in diluted solution is presented. The microbial biosensor is based on a three-dimensional interdigitated electrode array (3D-IDEA) impedimetric transducer with immobilized E. coli bacteria. In 3D-IDEA to increase the sensitivity to superficial impedance changes the electrode digits are separated by insulating barriers. A novel strategy is employed to selectively immobilize bacteria in the spaces over the electrode digits between the barriers, referred to here as trenches, in order to concentrate bacteria, improve the reproducibility of the E. coli immobilization and increase the sensitivity for monitoring bacterial response. For effective attachment of bacteria within the trenches an initial anchoring layer of a highly charged polycation, polyethyleneimine (PEI), was used. To facilitate immobilization of bacteria within the trenches and prevent their deposition on top of the barriers an important novelty is the use of poly( N -isopropylmethacrylamide) p(NIPMAM) microgels working as antifouling agents, deposited on top of the barriers by microcontact printing. The reported microbial biosensor approach allows the bacterial response to ampicillin, a bacteriolytic antibiotic, to be registered by means of impedance variations in a rapid and label-free operation that enables new possibilities in bioassays for toxicity testing.